TC4 titanium alloy wear-resistant anticorrosive coating for maritime work equipment as well as preparation method and application of TC4 titanium alloy wear-resistant anticorrosive coating
By combining ultrafast picosecond laser etching and microarc oxidation technology, a microarc oxidation composite coating with high hardness and high binding strength is generated, and micropore repair is carried out, which solves the problems of easy peeling of the coating and insufficient performance in the prior art, and significantly improves the corrosion resistance and wear resistance of titanium alloy components.
Patent Information
- Application Number
- CN202510042713.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The coatings generated by the existing microarc oxidation technology in marine service environments are prone to peel off, and there are micropores and cracks on the surface of the oxide layer, which reduces the wear and corrosion resistance of titanium alloy components.
Ultrafast picosecond laser etching and microarc oxidation technology are used to generate a microarc oxidation composite coating with high hardness and high binding strength, and micropore repair of the coating through ultrafast picosecond laser to improve the density and performance of the coating.
It significantly improves the corrosion resistance and wear resistance of the surface of TC4 titanium alloy, reduces the friction coefficient and self-corrosion current, enhances the hydrophobic performance, and extends the service life of the material.
Smart Images

Figure CN119824508A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the application field of material surface modification technology for marine engineering equipment, and in particular relates to a TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine engineering equipment, and a preparation method and application thereof. Background Art
[0002] With the continuous increase in deep-sea scientific research tasks and the continuous rise in demand for marine energy extraction, the demand for lightweight and corrosion-resistant marine engineering equipment materials is becoming increasingly urgent. Due to long-term immersion in seawater, marine engineering equipment has higher requirements for the comprehensive performance of the metal materials used in its construction. It must have good strength to withstand wind and waves and reduce the damage to marine engineering equipment caused by seawater impact, and it must also have excellent corrosion resistance to reduce the damage caused by the marine atmosphere and seawater to marine engineering equipment, so that it can meet the requirements of durability, corrosion resistance, stability and reliability during use, and at the same time, it must try its best to meet the requirements of lightweight, cost reduction, and increased service life.
[0003] As a new generation of lightweight alloys, titanium alloys have a series of advantages such as good corrosion resistance, excellent mechanical properties, and high specific strength. They are widely used in the field of marine engineering equipment, such as submarines and submersibles, ships, offshore drilling pipelines, seawater pipelines, seawater desalination equipment, etc. Among them, TC4 titanium alloy is an α+β duplex titanium alloy with high specific strength, low density, and non-magnetic properties. Its corrosion and wear behavior in the marine environment has always been a hot topic of research at home and abroad. Faced with harsh marine service environments, TC4 titanium alloys may suffer from performance failures such as fatigue, corrosion, and wear, and these problems usually start from the surface of the material. In order to solve these problems, large economic investments and long repair cycles are required. Therefore, the use of appropriate surface modification technology to further improve the corrosion and wear resistance of TC4 titanium alloy components is an effective way to solve this problem.
[0004] Commonly used titanium alloy surface treatment technologies include surface deformation strengthening technology, surface alloying technology, and surface coating technology. Surface deformation strengthening technologies for titanium alloy materials include shot peening, ultrasonic rolling, laser impact, and high-current pulsed electron beam strengthening. These strengthening technologies cause plastic deformation on the surface of the substrate, thereby improving the mechanical strength, fatigue resistance, and wear resistance of the material. They are usually used as basic treatment methods or combined with other strengthening technologies for strengthening. Common titanium alloy surface alloying technologies include carburizing, nitriding, plasma diffusion heat treatment, and ion implantation. These treatment technologies change the surface composition of the material by introducing modified atoms, thereby improving the hardness and wear resistance and corrosion resistance of the material. However, carburizing, nitriding, and plasma diffusion heat treatment still have shortcomings such as high energy consumption and high pollution. Although ion implantation has the advantages of uniform implantation of elements and strong bonding with the matrix, the depth of the ion implantation layer is shallow and it is easy to disappear in the form of wear debris. The surface coating technology of titanium alloy is a method of covering the surface of the material with a functional protective film layer without changing the surface composition of the substrate. It includes thermal spraying, laser cladding, chemical plating, electroplating, vapor deposition, anodizing and micro-arc oxidation. These methods generally have the defects of high heat input, complex plating solution composition, thin oxide film thickness and porous film layer.
[0005] As an advanced and green high-pressure plasma electrolytic oxidation surface treatment technology, micro-arc oxidation (MAO) technology can form a high-hardness ceramic oxide layer on the surface of valve metals such as titanium alloys, magnesium alloys and aluminum alloys, thereby improving the wear resistance and corrosion resistance of the titanium alloy surface. Micro-arc oxidation technology has obvious advantages in surface coating technology. The coating formed is uniform and not easy to decompose. It is convenient for pre-treatment, has low pollution, controllable electrical parameters and electrolyte composition, and has no special requirements for the shape of the workpiece.
[0006] However, during the micro-arc oxidation process, the composition and concentration of the electrolyte will have a great influence on the growth mechanism, bonding force and tribological properties of the film layer. The generated micro-arc oxidation coating is brittle and prone to coating peeling. At the same time, due to high-voltage discharge, a large number of micropores and cracks often occur on the surface of the oxide layer. In the marine service environment, this allows corrosive ions to penetrate into the substrate, which will weaken the wear and corrosion resistance of the coating. As a result, the long-term protection ability of the micro-arc oxidation coating is deteriorated. Faced with the harsh marine service environment, how to make full use of the advantages of the micro-arc oxidation surface modification process to generate a micro-arc oxidation coating with good coating-substrate bonding strength, high hardness and high density, and further improve the corrosion and wear resistance of titanium alloy components is an urgent problem to be solved. Summary of the invention
[0007] The purpose of the present invention is to provide a TC4 titanium alloy wear-resistant and anti-corrosion coating for marine engineering equipment, and a preparation method and application thereof, in order to solve the problems existing in the above-mentioned prior art. The micro-arc oxidation high-hardness coating can well isolate the metal substrate from the external environment, so that the metal components have good wear resistance and corrosion resistance. The present invention aims to improve the wear resistance and corrosion resistance of the micro-arc oxidation coating on the surface of titanium alloy. By taking advantage of the high energy density and cold processing of ultrafast picosecond lasers, the present invention combines ultrafast picosecond laser etching and micro-arc oxidation technology to generate a micro-arc oxidation composite coating with high hardness and high bonding strength. The micro-arc oxidation coating is repaired with the help of ultrafast picosecond lasers to further improve the wear resistance, corrosion resistance and self-cleaning performance of the micro-arc oxidation coating.
[0008] One of the technical solutions provided by the present invention:
[0009] A method for preparing a TC4 titanium alloy wear-resistant and anti-corrosion coating for marine engineering equipment comprises the following steps: sequentially performing ultrafast picosecond laser etching treatment, micro-arc oxidation treatment and ultrafast picosecond laser micropore repair on a pretreated TC4 titanium alloy substrate to prepare the TC4 titanium alloy wear-resistant and anti-corrosion coating for marine engineering equipment.
[0010] The titanium alloy surface composite coating using micro-arc oxidation treatment and ultrafast picosecond laser micropore repair technology adopted in the present invention can significantly reduce the holes on the coating surface, thereby achieving a micropore repair effect, thereby improving its wear resistance, corrosion resistance and self-cleaning performance in a marine environment.
[0011] Preferably, the parameters of the ultrafast picosecond laser etching process are: speed of 100 mm / s, number of times of 5 times, frequency of 40 kHz, power of 50 W, etching grid type: 200 μm×200 μm.
[0012] The present invention makes full use of the advantages of ultrafast picosecond laser etching, and by changing the micro-nanostructure of the substrate surface, enhances the hardness of the micro-arc oxidation coating and the bonding strength with the substrate. At the same time, ultrafast picosecond laser processing can increase the laser processing speed. Compared with traditional laser surface treatment technology, it can complete the same workload in a shorter time, thus improving production efficiency.
[0013] Preferably, the electrolyte components required for the micro-arc oxidation treatment include 15-20 g / L of sodium hexametaphosphate, 2-4 g / L of potassium hydroxide, 1-3 g / L of potassium fluoride, 15-20 g / L of sodium citrate and 1-3 g / L of sodium tungstate.
[0014] Preferably, the micro-arc oxidation treatment adopts a six-stage voltage transition to the final micro-arc oxidation voltage, the voltage transitions from 220V to 380V, the frequency is 500Hz, and the duty cycle is 10%.
[0015] More preferably, the six-stage voltages are 220V, 250V, 280V, 300V, 350V and 380V respectively, wherein the slow-start time of the output voltages 220V, 250V, 280V, 300V and 350V are all 5s, and the working time is 30s, and the slow-start time of the output voltage 380V is 5s, and the working time is 210s.
[0016] When the voltage regulation is changed, for example, the roughness of the TC4 titanium alloy micro-arc oxidation coating prepared with the six-stage output voltage of 250V, 280V, 300V, 350V, 400V, and 450V is visible to the naked eye. When the voltage regulation is changed, for example, the six-stage output voltage is 180V, 200V, 250V, 280V, 300V, and 350V, the prepared TC4 titanium alloy micro-arc oxidation coating is incomplete and easy to peel off. Too high a voltage will directly affect the roughness of the micro-arc oxidation coating surface, and too low a voltage will not generate a complete micro-arc oxidation coating. The appropriate output voltage is the key factor in forming a complete and dense micro-arc oxidation coating.
[0017] According to the characteristics of the phosphate electrolyte system, the present invention prepares a suitable electrolyte, adjusts excellent six-stage voltage to expand the micro-arc oxidation power supply parameters, and generates a micro-arc oxidation coating with a uniform surface.
[0018] Preferably, the parameters of the ultrafast picosecond laser microhole repair are: speed of 100 mm / s, number of times of 5 times, frequency of 40 Hz, power of 50 W, and repair grid type of 200 μm×200 μm.
[0019] The present invention repairs the surface micropores of the micro-arc oxidation coating by ultrafast picosecond laser, which can further improve the compactness of the micro-arc oxidation coating, thereby improving the wear resistance and corrosion resistance of the material. At the same time, the high precision of ultrafast picosecond laser processing can greatly reduce material waste and improve material utilization.
[0020] The second technical solution provided by the present invention is:
[0021] A TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine engineering equipment prepared by the above-mentioned preparation method.
[0022] The third technical solution provided by the present invention is:
[0023] An application of the above-mentioned TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine engineering equipment in marine engineering equipment.
[0024] Compared with the prior art, the present invention has the following advantages and technical effects:
[0025] The present invention further improves the corrosion resistance and wear resistance of the TC4 titanium alloy surface coating. The substrate is pre-treated by ultrafast picosecond laser etching technology, which can effectively improve the surface hardness of the TC4 titanium alloy. The micro-arc oxidation coating formed by phosphate-based electrolyte is repaired by ultrafast picosecond laser micropores. Compared with the TC4 titanium alloy substrate, the hardness is greatly improved, the friction coefficient is reduced, the self-corrosion current is significantly reduced, and the hydrophobicity is also improved. When facing harsh marine environments, the corrosion resistance, wear resistance and self-cleaning properties of the TC4 titanium alloy surface can be greatly improved.
[0026] The preparation process of the ultrafast picosecond laser etching-micro-arc oxidation-ultrafast picosecond laser micropore repair composite coating adopted by the present invention is simple, easy to operate and eco-friendly. The TC4 titanium alloy wear-resistant and corrosion-resistant coating provided by the present invention has the characteristic of adjustable structure. In the preparation of the electrolyte, any reagent elements that may cause pollution to the marine environment are strictly eliminated to ensure that the entire process is green and environmentally friendly. In the micro-arc oxidation process, the excellent six-stage voltage-controlled micro-arc oxidation treatment technology is debugged to generate a micro-arc oxidation composite coating with strong bonding, wear resistance and corrosion resistance on the surface of the TC4 titanium alloy.
[0027] The ultrafast picosecond laser etching pre-treatment and micropore repair post-treatment processes adopted in the present invention can realize the transformation of the titanium alloy surface from hydrophilic to hydrophobic, thereby achieving the purpose of self-cleaning, and can increase its service life and save costs in harsh marine service environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0029] Figure 1 This is a flow chart of preparing TC4 titanium alloy wear-resistant and corrosion-resistant coatings according to Example 1 and Comparative Examples 1-3 of the present invention;
[0030] Figure 2 The microscopic morphology of the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3;
[0031] Figure 3 The microhardness distribution diagram of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3;
[0032] Figure 4 The friction coefficient-friction time curves of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3;
[0033] Figure 5 The potentiodynamic polarization curves of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3 are shown;
[0034] Figure 6 This is the static contact angle test diagram of TC4 titanium alloy substrate;
[0035] Figure 7 This is a static contact angle test diagram of the TC4 titanium alloy coating (LST+MAO+LST) prepared in Example 1;
[0036] Figure 8 This is a static contact angle test diagram of the TC4 titanium alloy coating (MAO) prepared in Comparative Example 1;
[0037] Fig. 9 This is a static contact angle test diagram of the TC4 titanium alloy coating (MAO+LST) prepared in Comparative Example 2;
[0038] Fig.10 This is the static contact angle test diagram of the TC4 titanium alloy coating (LST+MAO) prepared in Comparative Example 3. DETAILED DESCRIPTION
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] The room temperature in the present invention refers to 20 to 30°C.
[0045] The present invention aims to improve the hardness, wear resistance and corrosion resistance of titanium alloy micro-arc oxidation coating, and proposes an environmentally friendly, simple, easy and efficient processing method for preparing a composite coating of ultrafast picosecond laser etching-micro-arc oxidation-ultrafast picosecond laser micropore repair. The method not only ensures the bonding strength between the coating and the substrate, but also greatly improves the surface hardness of the coating, reduces the friction coefficient and self-corrosion current, realizes the transformation from hydrophilicity to hydrophobicity of the material surface, and effectively improves the corrosion resistance and anti-corrosion properties of the titanium alloy surface. Figure 1 This is a flow chart of preparing TC4 titanium alloy wear-resistant and corrosion-resistant coatings according to Example 1 and Comparative Examples 1-3 of the present invention.
[0046] Titanium alloy micro-arc oxidation coating: A process that applies high voltage in the electrolyte to induce micro-area arc discharge on the surface of the titanium alloy, thereby forming a hard oxide ceramic film on the surface of the material. This film can significantly improve the wear resistance and corrosion resistance of the titanium alloy.
[0047] Ultrafast picosecond laser etching: Combining the high energy density and cold processing characteristics of ultrafast picosecond lasers, the titanium alloy substrate is subjected to ultrafast etching pre-treatment. By changing the micro-nano structure of the titanium alloy surface, the hardness of the micro-arc oxidation coating and the bonding strength with the substrate are enhanced, while the friction coefficient of the micro-arc oxidation coating is reduced to further improve the wear resistance of the material.
[0048] Ultrafast picosecond laser micropore repair: The micropores of the formed microarc oxidation coating are repaired by ultrafast picosecond laser, thereby reducing the pores and enhancing the density of the coating. This technology significantly improves the wear resistance and corrosion resistance of the material, and is suitable for material technology applications with high requirements for wear and corrosion resistance. The hardness of the microarc oxidation coating after ultrafast picosecond laser etching pre-treatment and micropore repair post-treatment is greatly improved, the friction coefficient is reduced, the corrosion current is reduced, and the material surface is transformed from hydrophilic to hydrophobic, effectively extending the service life of titanium alloy parts.
[0049] The micro-arc oxidation electrolyte plays a vital role in the micro-arc oxidation process. The components in the electrolyte, such as silicates, aluminates and phosphates, can promote the passivation of the metal surface and form a thin dielectric insulating film. As a conductive solution medium, the electrolyte can transfer the energy required for the oxidation reaction at the metal substrate / electrolyte interface; during the micro-arc discharge process, specific components in the electrolyte (such as ions, ion clusters, molecules, etc.) can enter the coating through chemical reactions or electrophoresis mechanisms, thereby further modifying, improving or designing novel coatings. The micro-arc oxidation electrolyte components prepared in the embodiment of the present invention include sodium hexametaphosphate 15-20g / L, potassium hydroxide 2-4g / L, potassium fluoride 1-3g / L, sodium citrate 15-20g / L and sodium tungstate 1-3g / L. The preferred micro-arc oxidation electrolyte components of the embodiment of the present invention are sodium hexametaphosphate 20g / L, potassium hydroxide 4g / L, potassium fluoride 3g / L, sodium citrate 20g / L and sodium tungstate 3g / L.
[0050] The functional parameters of the ultrafast picosecond laser used in the embodiment of the present invention can be adjusted within the following ranges: laser power 50W, wavelength 1030nm, maximum single pulse energy 25μJ, repetition frequency 20-2750kHz, pulse width 1-3ps, and beam quality M2<1.4.
[0051] The functional parameters of the micro-arc oxidation power supply used in the embodiment of the present invention are as follows: voltage-stabilized pulse mode, output voltage 1V to 750V adjustable, pulse frequency 100Hz to 2000Hz adjustable, pulse width 5% to 95% adjustable.
[0052] Example 1 A method for preparing a TC4 titanium alloy wear-resistant and anti-corrosion coating for marine equipment
[0053] S1. First, the TC4 titanium alloy substrate was polished with 400#, 800#, 1200#, and 2000# silicon carbide sandpaper, then ultrasonically degreased with acetone, and then ultrasonically cleaned with ethanol and deionized water in sequence, and naturally air-dried. The resulting sample was named TC4;
[0054] S2. Ultrafast picosecond laser etching of TC4: Place the TC4 titanium alloy substrate prepared in S1 on the three-axis moving platform of the ultrafast picosecond laser, control the movement of the X, Y and Z axes, and the laser source is controlled by a computer to perform grid etching on the surface of the substrate using ultrafast picosecond laser. Ultrafast picosecond laser etching processing parameters: speed: 100 mm / s, number of times: 5 times, frequency: 40 kHz, power: 50 W, etching grid type: 200 μm × 200 μm, take out the treated substrate, wash it with deionized water, and air dry it naturally. The obtained sample is named LST;
[0055] S3. Micro-arc oxidation treatment of the LST prepared by S2: Using the LST sample as the anode and the stainless steel plate as the cathode, the appropriate micro-arc oxidation power supply parameters are adjusted at room temperature to carry out micro-arc oxidation treatment. The specific operation is as follows: The LST is placed in an electrolytic cell with a prepared electrolyte (sodium hexametaphosphate 20g / L, potassium hydroxide 4g / L, potassium fluoride 3g / L, sodium citrate 20g / L, sodium tungstate 3g / L) through a copper wire. In order to ensure a continuous and uniform reaction between the electrolyte and the sample, air is continuously introduced into the electrolyte (flow rate 0.5L / min). The micro-arc oxidation process adopts a voltage-stabilized pulse mode with a frequency of 500Hz and a duty cycle of 10%. In order to ensure the surface energy of the titanium alloy A micro-arc oxidation film layer was uniformly generated, and a six-stage voltage transition was adopted to the final micro-arc oxidation voltage. The voltage transitioned from 220V to 380V. The entire micro-arc oxidation time was 6.5min, including 220V (working time 30s, slow start time 5s), 250V (working time 30s, slow start time 5s), 280V (working time 30s, slow start time 5s), 300V (working time 30s, slow start time 5s), 350V (working time 30s, slow start time 5s), 380V (working time 210s, slow start time 5s). The treated samples were taken out, washed with deionized water, and naturally air-dried. The obtained samples were named LST+MAO.
[0056] S4. The surface of the LST+MAO sample was repaired with ultrafast picosecond laser micropores using an ultrafast picosecond laser. The processing parameters were: speed: 100 mm / s, number of times: 5 times, frequency: 40 Hz, power: 50 W, repair grid type: 200 μm × 200 μm. The treated substrate was taken out, washed with deionized water, and air-dried naturally. The obtained sample was named LST+MAO+LST.
[0057] Comparative Example 1
[0058] The same as Example 1, except that the ultrafast picosecond laser etching and ultrafast picosecond laser micropore repairing treatment are not performed. The specific preparation method is as follows:
[0059] S1. First, the TC4 titanium alloy substrate was polished with 400#, 800#, 1200#, and 2000# silicon carbide sandpaper, then ultrasonically degreased with acetone, and then ultrasonically cleaned with ethanol and deionized water in sequence, and naturally air-dried. The resulting sample was named TC4;
[0060] S2. The stainless steel plate is used as the cathode, and the appropriate micro-arc oxidation power supply parameters are adjusted at room temperature to carry out micro-arc oxidation treatment. The specific operation is as follows: the TC4 substrate obtained in S1 is placed in an electrolytic cell with a prepared electrolyte (sodium hexametaphosphate 20g / L, potassium hydroxide 4g / L, potassium fluoride 3g / L, sodium citrate 20g / L, sodium tungstate 3g / L) through a copper wire. In order to ensure the continuous and uniform reaction of the electrolyte and the sample, air is continuously introduced into the electrolyte (flow rate 0.5L / min). The micro-arc oxidation process adopts a voltage-stabilized pulse mode with a frequency of 500Hz and a duty cycle of 10%. In order to ensure that a micro-arc oxidation film can be uniformly generated on the surface of the titanium alloy, A six-stage voltage transition was adopted to the final micro-arc oxidation voltage, and the voltage transitioned from 220V to 380V. The entire micro-arc oxidation time was 6.5min, including 220V (working time 30s, slow start time 5s), 250V (working time 30s, slow start time 5s), 280V (working time 30s, slow start time 5s), 300V (working time 30s, slow start time 5s), 350V (working time 30s, slow start time 5s), 380V (working time 210s, slow start time 5s). The treated samples were taken out, washed with deionized water, and naturally air-dried. The obtained samples were named MAO.
[0061] Comparative Example 2
[0062] The same as Example 1, except that ultrafast picosecond laser etching is not performed. The specific preparation method is as follows:
[0063] S1. First, the TC4 titanium alloy substrate was polished with 400#, 800#, 1200#, and 2000# silicon carbide sandpaper, then ultrasonically degreased with acetone, and then ultrasonically cleaned with ethanol and deionized water in sequence, and naturally air-dried. The resulting sample was named TC4;
[0064] S2. Use the stainless steel plate as the cathode and adjust the appropriate micro-arc oxidation power supply parameters at room temperature to carry out micro-arc oxidation treatment. The specific operation is as follows: Place the TC4 substrate obtained in S1 in an electrolytic cell prepared with electrolyte (sodium hexametaphosphate 20g / L, potassium hydroxide 4g / L, potassium fluoride 3g / L, sodium citrate 20g / L, sodium tungstate 3g / L) through a copper wire. In order to ensure the continuous and uniform reaction of the electrolyte and the sample, air is continuously introduced into the electrolyte (flow rate 0.5L / min). The micro-arc oxidation process adopts a voltage-stabilized pulse mode with a frequency of 500Hz and a duty cycle of 10%. In order to ensure that a micro-arc oxidation film can be uniformly formed on the surface of the titanium alloy, A six-stage voltage transition was adopted to the final micro-arc oxidation voltage, and the voltage transitioned from 220V to 380V. The entire micro-arc oxidation time was 6.5min, including 220V (working time 30s, slow start time 5s), 250V (working time 30s, slow start time 5s), 280V (working time 30s, slow start time 5s), 300V (working time 30s, slow start time 5s), 350V (working time 30s, slow start time 5s), 380V (working time 210s, slow start time 5s). The treated samples were taken out, washed with deionized water, and naturally air-dried. The obtained samples were named MAO.
[0065] S3. The surface of the MAO sample was repaired with ultrafast picosecond laser micropores using an ultrafast picosecond laser. The processing parameters were: speed: 100 mm / s, number of times: 5 times, frequency: 40 Hz, power: 50 W, repair grid type: 200 μm × 200 μm. The treated substrate was taken out, washed with deionized water, and air-dried naturally. The obtained sample was named MAO+LST.
[0066] Comparative Example 3
[0067] The same as Example 1, except that the ultrafast picosecond laser micropore repairing treatment is not performed. The specific preparation method is as follows:
[0068] S1. First, the TC4 titanium alloy substrate was polished with 400#, 800#, 1200#, and 2000# silicon carbide sandpaper, then ultrasonically degreased with acetone, and then ultrasonically cleaned with ethanol and deionized water in sequence, and naturally air-dried. The resulting sample was named TC4;
[0069] S2. Place the TC4 titanium alloy substrate prepared in S1 on the three-axis moving platform of the ultrafast picosecond laser, control the movement of the X, Y and Z axes, and the laser source is controlled by a computer to perform grid etching on the surface of the substrate using ultrafast picosecond laser. Ultrafast picosecond laser etching processing parameters: speed: 100 mm / s, number of times: 5 times, frequency: 40 kHz, power: 40 W, etching grid type: 200 μm × 200 μm, take out the treated substrate, wash it with deionized water, and air dry it naturally. The obtained sample is named LST;
[0070] S3. With LST as anode and stainless steel plate as cathode, the appropriate micro-arc oxidation power supply parameters were adjusted at room temperature to carry out micro-arc oxidation treatment. The specific operation was as follows: LST was placed in an electrolytic cell prepared with electrolyte (sodium hexametaphosphate 20g / L, potassium hydroxide 4g / L, potassium fluoride 3g / L, sodium citrate 20g / L, sodium tungstate 3g / L) through a copper wire. In order to ensure the continuous and uniform reaction between the electrolyte and the sample, air was continuously introduced into the electrolyte (flow rate 0.5L / min). The micro-arc oxidation process adopted a voltage-stabilized pulse mode with a frequency of 500Hz and a duty cycle of 10%. In order to ensure that a micro-arc oxidation film can be uniformly formed on the surface of the titanium alloy, the A six-stage voltage transition was used to the final micro-arc oxidation voltage, and the voltage transitioned from 220V to 380V. The entire micro-arc oxidation time was 6.5min, including 220V (working time 30s, slow start time 5s), 250V (working time 30s, slow start time 5s), 280V (working time 30s, slow start time 5s), 300V (working time 30s, slow start time 5s), 350V (working time 30s, slow start time 5s), 380V (working time 210s, slow start time 5s). The treated samples were taken out, washed with deionized water, and naturally air-dried. The obtained samples were named LST+MAO.
[0071] Performance test
[0072] 1. Morphology analysis of TC4 titanium alloy coating
[0073] The surface morphology of the TC4 titanium alloy coatings prepared in Example 1 and Comparative Examples 1-3 was analyzed under a scanning electron microscope, and the scanning electron microscope model was Czech TESCAN MIRALMS. Each sample (MAO, MAO+LST, LST+MAO, and LST+MAO+LST) was directly adhered to the conductive adhesive, and gold was sprayed for 45 seconds using a Quorum SC7620 sputtering coater, and the gold spraying current was 10mA; then, the sample morphology was photographed using a TESCAN MIRA LMS scanning electron microscope, and the acceleration voltage during the morphology photography was 3kV.
[0074] Figure 2The microscopic morphology of the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3 is shown in FIG. Figure 2 It can be seen that the average hole diameter of the MAO coating (Comparative Example 1) is about 4.7 microns, and the average hole diameter of the LST+MAO coating (Comparative Example 3) is about 2.2 microns. It can be seen that the MAO coating treated before ultrafast picosecond laser etching has smaller holes; the morphology of the MAO+LST coating (Comparative Example 2) shows that the MAO coating treated after ultrafast picosecond laser micropore repair forms a fused mass, completes the coating repair and pore sealing, and the MAO coating is dense. The morphology of the LST+MAO+LST coating (Example 1) shows that the size of the fused mass of the MAO coating combined with ultrafast picosecond laser etching pre-treatment and micropore repair post-treatment is more uniform, ensuring the flatness of the coating surface.
[0075] 2. Hardness test
[0076] The hardness test of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3 was conducted using a MHVD-1000AT digital microhardness tester. The average value was obtained by ten-point testing, with the test point 1 cm from the center of the sample surface. 2 Within the range of , 10 points are randomly selected for measurement, the applied load is 1000g, and the load duration is 10s.
[0077] Figure 3 The microhardness distribution diagram of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3. Figure 3 It can be seen that the Vickers microhardness of the four micro-arc oxidation coatings is higher than that of the TC4 titanium alloy substrate. After calculation, the average of the measurement values of 10 points is taken. The microhardness of the TC4 titanium alloy substrate is about 358HV, the microhardness of the MAO coating is about 817HV, the microhardness of the MAO+LST coating is about 976HV, the microhardness of the LST+MAO coating is about 862HV, and the microhardness of the LST+MAO+LST coating is about 1105HV. Among them, the hardness of the LST+MAO+LST coating is the highest, and the hardness is increased by about 3.1 times compared with the substrate. That is, the composite coating treated before ultrafast picosecond laser etching and treated after micropore repair shows a higher hardness.
[0078] 3. Friction test
[0079] The friction test was conducted on the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3. The friction and wear tester used was an SFT-2M pin-on-disc friction and wear tester. The GCr15 ball is used for the test, the test load is 2N, the rotation speed is 100r / min, the rotation radius is 2mm, and the time is 30min. According to the above set parameters, the friction coefficient of the coating is automatically detected in real time by the computer through the ball-disc friction pair test.
[0080] Figure 4 The friction coefficient-friction time curves of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3 are shown in FIG. Figure 4 It can be seen that after the friction stabilizes (after 10 minutes of friction), the friction coefficients of the four micro-arc oxidation coatings are all lower than that of the TC4 titanium alloy substrate, among which the friction coefficient of the TC4 titanium alloy substrate is about 0.49, the friction coefficient of the MAO coating is about 0.36, the friction coefficient of the MAO+LST coating is about 0.27, the friction coefficient of the LST+MAO coating is about 0.30, and the friction coefficient of the LST+MAO+LST coating is about 0.26. The LST+MAO+LST coating exhibits the lowest friction coefficient, which is about 47% lower than the substrate, that is, the composite coating treated with ultrafast picosecond laser etching before and micropore repair after shows good wear resistance, and the friction coefficient tends to decrease in the later stage of friction.
[0081] 4. Corrosion resistance test
[0082] The corrosion performance of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3 was tested. The electrochemical workstation used was a Wuhan Cost CS350S electrochemical workstation, which adopted the traditional three-electrode working mode. The area of the working electrode exposed in the solution was 1 cm 2 The test samples were tested with platinum foil as the auxiliary electrode and saturated calomel electrode (SCE) as the reference electrode. A 3.5% NaCl solution was used to simulate seawater solution. Each sample was first soaked in a 3.5% NaCl solution for 4 hours. After the open circuit was stabilized, a potentiodynamic polarization test was performed. The scan rate was set to 1mv / s in the range of -0.5V to 0.5V (relative OCP).
[0083] Figure 5 The potentiodynamic polarization curves of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3. The self-corrosion current of the TC4 titanium alloy substrate is 4.56×10 -10 A / cm 2 The self-corrosion current of LST+MAO+LST coating is the smallest, which is 4.10×10 -11 A / cm 2 The self-corrosion current is one order of magnitude lower than that of the TC4 substrate, that is, the composite coating pre-treated by ultrafast picosecond laser etching and post-treated by micropore repair has better corrosion resistance.
[0084] 5. Contact angle test
[0085] The contact angle test was performed on the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1 and Comparative Examples 1-3. The contact angle measuring instrument used was an SDC-200S scientific contact angle measuring instrument, and a 10 μL water droplet was used to evaluate the horizontal static contact angle on the sample surface. Samples with a contact angle of less than 90° exhibited hydrophilic characteristics, and samples with a contact angle of greater than 90° exhibited hydrophobic characteristics. When exhibiting hydrophobic characteristics, the larger the contact angle, the better the hydrophobic performance.
[0086] Figure 6-10 The static contact angle test diagrams of the TC4 titanium alloy substrate, the TC4 titanium alloy coating prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in sequence. Figure 6-10 It can be seen that the TC4 titanium alloy substrate exhibits hydrophilicity. After micro-arc oxidation treatment, the four micro-arc oxidation coatings all exhibit hydrophobicity, among which the static contact angle of the TC4 titanium alloy substrate is about 77.34°, the static contact angle of the MAO coating is about 92.15°, the static contact angle of the MAO+LST coating is about 98.53°, the static contact angle of the LST+MAO coating is about 111.18°, and the static contact angle of the LST+MAO+LST coating is about 109.29°. The static contact angle of the LST+MAO coating is the largest, followed by the LST+MAO+LST coating. Compared with the substrate, the hydrophilic and hydrophobic properties of the coating surface have changed, and the hydrophobic coating is more conducive to achieving the self-cleaning property of the coating surface and slowing down the corrosion rate of the titanium alloy.
[0087] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine equipment, characterized in that: The following steps are involved: The pretreated TC4 titanium alloy substrate is subjected to ultrafast picosecond laser etching treatment, micro-arc oxidation treatment and ultrafast picosecond laser micropore repair in sequence to prepare the TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine engineering equipment.
2. The method for preparing the TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine equipment according to claim 1, characterized in that: The parameters of the ultrafast picosecond laser etching process are: speed of 100 mm / s, number of times of 5 times, frequency of 40 kHz, power of 50 W, and etching grid type: 200 μm×200 μm.
3. The method for preparing the TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine equipment according to claim 1, characterized in that: The electrolyte components required for the micro-arc oxidation treatment include 15-20 g / L of sodium hexametaphosphate, 2-4 g / L of potassium hydroxide, 1-3 g / L of potassium fluoride, 15-20 g / L of sodium citrate and 1-3 g / L of sodium tungstate.
4. The method for preparing the TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine equipment according to claim 1, characterized in that: The micro-arc oxidation treatment adopts six-stage voltage transition to the final micro-arc oxidation voltage, the voltage transitions from 220V to 380V, the frequency is 500Hz, and the duty cycle is 10%.
5. The method for preparing the TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine equipment according to claim 5, characterized in that: The six-stage voltages are 220V, 250V, 280V, 300V, 350V and 380V respectively, wherein the slow-start time of the output voltages 220V, 250V, 280V, 300V and 350V are all 5s, and the working time is all 30s, and the slow-start time of the output voltage 380V is 5s, and the working time is 210s.
6. The method for preparing the TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine equipment according to claim 1, characterized in that: The parameters of the ultrafast picosecond laser microhole repair are: speed of 100 mm / s, number of times of 5 times, frequency of 40 Hz, power of 50 W, and repair grid type of 200 μm×200 μm.
7. A TC4 titanium alloy wear-resistant and corrosion-resistant coating for marine engineering equipment prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the TC4 titanium alloy wear-resistant and anti-corrosion coating for marine engineering equipment according to claim 7 in marine engineering equipment.